Pengaruh Pajak, Ukuran Perusahaan, Profitabilitas Terhadap Transfer Pricing Dengan Leverage Sebagai Variabel Moderasi (Stusi Empiris Perusahaan Manufaktur Sektor Makanan dan Minuman Tahun 2017-2021) - Gani Saputra (Jurnal Literasi Akuntansi, 2023)
Purpose: This study aims to show the effect of tax, company size and profitability on transfer pricing with leverage as a moderating variable. The nature of this research is quantitative. Methot:  The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 and there are 40 companies. The research sample used purposive sampling and obtained 15 companies. This research uses secondary data in the form of financial reports and company annual financial reports which are downloaded from www.idx.co.id and the website of each company that is the sample in this study. Data analysis using multiple linear analysis and moderate regression analysis. Finding: The results of this study indicate that taxes have a positive effect on transfer pricing. Company size has a positive effect on transfer pricing. Profitability has a positive effect on transfer pricing. Leverage can strengthen the positive effect of taxes on pricin transfers. Leverage can strengthen the positive influence of company size on transfer pricing. However, leverage cannot moderate the effect of profitability on transfer pricing.